World religions - Matthews, Warren
Presenting both the histories and the prevalent worldviews of the major world religions, Matthews' WORLD RELIGIONS methodically introduces students to the richness and diversity of these traditions. The "Worldview" sections in particular make this textbook the most helpful textbook when it comes to comparative analyses of the religions. In these sections students can see how the different religions understand a common set of ten themes that are fundamental to all traditions, including the nature of the Absolute, the place of humans in the world, rituals and symbols, and the prospects for life after death. Furthermore, this text combines insightful, engaging prose with maps, photographs, timelines, excerpts from sacred texts, and other helpful pedagogical aids, to employ a scholarly approach that neither shields students from current research nor encumbers them with it. Students are encouraged, individually and collectively, to pursue their own dialogues with the voices and nuances of these religions